Research on router device of OAM optical communication - Zhongyi GUO; Zhenzhen PAN; Chaofan GONG; Zikun WANG; Kai GUO; Hongping ZHOU (Tongxin xuebao)
With the development of orbital angular momentum (OAM) based optical communication technology,OAM router played an important role in improving the flexibility and practicability of OAM communication system.In recent years,the research on multifunctional OAM router had also been developed rapidly.Based on this,the research results on the OAM router had been summarized and reviewed,in which the principles,research methods,advantages and disadvantages of six types of OAM router,with the functions of switching,multicast,filtering,adding/extraction,and jumping and mode dividing respectively,had been discussed and summarized in details.Meanwhile,the future developing trend of the OAM router has also been prospected and discussed in the end.